Cover Picture: Vanadium Oxide Nanosheets for Flexible Dendrite‐Free Hybrid Aluminium‐Lithium‐Ion Batteries with Excellent Cycling Performance (Batteries & Supercaps 3/2019). Issue 3 (12th March 2019) - Gong, Xuefei; Chen, Jingwei; Li, Shaohui; Mohrhusen, Lars; Al‐Shamery, Katharina; Lee, Pooi See
Abstract : The Front Cover shows the hybrid Al‐Li‐ion batteries with Al as anode and mixed Al 3+ and Li + ions based electrolyte. Owing to the low cost, high volumetric capacities and dendrite‐free characteristics and improved kinetics of utilizing the mixed electrolytes, the hybrid Al‐Li‐ion batteries deliver competitive advantages among various energy storage devices. More information can be found in theArticle by P. S. Lee et al .